Company management systems models evaluation - Shi Lin; A. V. Bodyako (Вестник университета)
In order to form all elements of company management, it is necessary to choose the right management model that fully corresponds to the peculiarities of the sphere of existence, the personnel’s needs and the activity goals.   The purpose of the study is to examine the management systems existing models and evaluate them with regard to their use in Russian companies.   Within the framework of the work, theoretical and empirical methods were used to analyze the existing management experience. Studies of Russian and foreign specialists in the field of evaluation of management systems existing models and their effectiveness have been studied. In the course of the work it has been revealed that each of the existing national management systems was formed over many years, based on the peculiarities of the employees’ mentality and the market specifics. The American and European systems are more focused on obtaining economic results (profit), and the Japanese and Arab systems are more focused on meeting the needs of society and their employees. Each of them is to a certain extent effective within the framework of its state, but their application in other countries requires considerable adaptation. In recent years, several new management models have been developed that are able to adapt to environmental changes and are aimed at high performance. In Russian companies, modern models may be the most effective (marketing, “full” or integration models), but it is necessary to develop their own management systems to ensure high efficiency.